DAMPs from Cell Death to New Life - Vénéreau, Emilie; Ceriotti, Chiara; Bianchi, Marco Emilio (Frontiers in Immunology, 2015)
Our body handles tissue damage by activating the immune system in response to intracellular molecules released by injured tissues (Damage-Associated Molecular Patterns, DAMPs), in a similar way as it detects molecular motifs conserved in pathogens (pathogen-associated molecular patterns, PAMPs). DAMPs are molecules that have a physiological role inside the cell, but acquire additional functions when they are released outside the cell: they alert the body about danger, stimulate an inflammatory response, and finally promote the regeneration process. Beside their passive release by dead cells, some DAMPs can be secreted or exposed by living cells undergoing a life-threatening stress. DAMPs have been linked to inflammation and related disorders: hence, inhibition of DAMP-mediated inflammatory responses is a promising strategy to improve the clinical management of infection- and injury-elicited inflammatory diseases. However, it is important to consider that DAMPs are not only danger signals but also central players in tissue repair. Indeed, some DAMPs have been studied for their role in tissue healing after sterile or infection-associated inflammation. This review is focused on two exemplary DAMPs, HMGB1 and ATP, and their contribution to both inflammation and tissue repair.